“Evaluación de la osmolalidad de la bebida energizante a base de tuna (opuntia ficus-indica) y guayusa (ilex guayusa)” - Jaguaco Proaño, Genderson David (2023)
In the present research study, the creation of an innovative energizing beverage has been carried out, based on the combination of two ancestral ingredients: prickly pear (Opuntia ficus-indica) and guayusa (Ilex guayusa). The main purpose of the study was to maximize the use of the ancestral prickly pear fruit, which is poorly commercialized, by combining its valuable nutritional properties with those of guayusa. A rigorous complete random experimental design has been used, which involved the use of four key factors, A + B + C + D, with levels of prickly pear pulp concentration as factor A, guayusa infusion as factor B, type of salts as factor C, and water as factor D, respectively. As a result, a total of 13 treatments have been obtained, which have been thoroughly evaluated through the Design Expert 22.0.2 program. Through a comprehensive sensory analysis with a group of university students, it has been determined that treatment 11 is the most accepted. It is important to highlight that thanks to the Design Expert 22.0.2 program, it has been possible to accurately verify that treatment 11 is the best of all the treatments analyzed. This particular treatment has been shown to contain the following concentrations: 70% prickly pear pulp, 20% guayusa infusion, 0.44% salts, and 9.55% water. In order to ensure the safety and quality of the energizing beverage, a series of physical chemical, proximal, and nutritional analyses have been carried out to verify if treatment 11 complies with the standards established by Ecuadorian regulations. The results obtained regarding titratable acidity (9%), pH (5.44), total solids (10.15%), and density (0.96 g/ml) have been carefully compared with the INEN 2304, 2017 standard, and it has been found that they are within the established range. In addition, it has been verified that osmolality (553 mmol/kg) and conductivity (2.37 μS/cm) comply with the standards established by FDA (Food and Drug Administration) and Colombian regulations, respectively. The microbiological analyses carried out on treatment 11 have revealed a quantity of mesophilic aerobes CFU/g